Eugenol Attenuates Transmissible Gastroenteritis Virus-Induced Oxidative Stress and Apoptosis Via ROS-NRF2-ARE Signaling - Kang Wang; Yan Tang; Xiu Wu; Hongmin Liang; Daiwen Chen; Bing Yu; Jun He; Xiangbing Mao; Zhiqing Huang; Hui Yan; Aimin Wu; Yuheng Luo; et al. (MDPI AG, 2022)
Transmissible gastroenteritis virus (TGEV), a coronavirus that causes severe diarrhea due to oxidative stress in the piglet intestine, is a major cause of economic loss in the livestock industry. However, limited interventions have been shown to be effective in the treatment of TGEV. Here, we demonstrate the therapeutic activity of eugenol in TGEV-induced intestinal oxidative stress and apoptosis. Our data show that eugenol supplementation protects intestine and IPEC-J2 cells from TGEV-induced damage. Mechanistically, eugenol reduces TGEV-induced oxidative stress in intestinal epithelial cells by reducing reactive oxygen species levels. Interestingly, eugenol also inhibits TGEV-induced intestinal cell apoptosis in vitro and in vivo. In conclusion, our data suggest that eugenol prevents TGEV-induced intestinal oxidative stress by reducing ROS-mediated damage to antioxidant signaling pathways. Therefore, eugenol may be a promising therapeutic strategy for TGEV infection.